Remanufacturing as pathway for achieving circular economy for Indonesian SMEs - Fatimah, Y.; Biswas, Wahidul (2017)
© Springer International Publishing AG 2017. Remanufacturing could potentially offer economic and environmental benefits for Indonesian SMEs. The objective of this research is to explore as to how remanufacturing strategy could attain greater resource efficiency through resources consumption reduction and waste minimization. An assessment on resources efficiency has been performed for Indonesian remanufacturing SMEs producing auto parts. The value, contributions and limitations of remanufacturing for achieving resources efficiency were explored and some key issues including organizational, consumer behaviors and government incentives issues have been identified. Accordingly, national resources policy recommendations have been made. Future potential business value that enhances Indonesian economic, social and environmental pillars of sustainability through remanufacturing has been discussed in this paper.